2019
DOI: 10.1101/620450
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Clusters of sub-Saharan African countries based on sociobehavioural characteristics and associated HIV incidence

Abstract: ObjectiveHIV incidence varies widely between sub-Saharan African (SSA) countries. This variation coincides with a substantial sociobehavioural heterogeneity, which complicates the design of effective interventions. In this study, we investigated how socio-behavioural heterogeneity in sub-Saharan Africa could account for the variance of HIV incidence between countries.MethodsWe used unsupervised machine learning to analyse data from the Demographic and Health Surveys of 29 SSA countries completed after 2010. We… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2019
2019
2020
2020

Publication Types

Select...
1
1

Relationship

2
0

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 51 publications
0
3
0
Order By: Relevance
“…Efforts should be made to increase the coverage of HIV testing in particular among these sub-populations. 2 Cannot read at all, or can read part of a sentence only 3 We defined the prevalence as the proportion of positive tests among the conclusive (positive and negative) tests results 10.0% 6.4% 0.8% 13.0% 0.5% 3.9% 4 Can read a whole sentence 5 Cannot read at all, or can read part of a sentence only 6 Sexually Transmitted Infection 7 We defined the prevalence as the proportion of positive tests among the conclusive (positive and negative) tests results. 3 -"adolescent, literate, never married" 4 -"over 35, married, media access" 5 -"adolescent, illiterate, never married" 6 -"20-35 years, married, media access"…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Efforts should be made to increase the coverage of HIV testing in particular among these sub-populations. 2 Cannot read at all, or can read part of a sentence only 3 We defined the prevalence as the proportion of positive tests among the conclusive (positive and negative) tests results 10.0% 6.4% 0.8% 13.0% 0.5% 3.9% 4 Can read a whole sentence 5 Cannot read at all, or can read part of a sentence only 6 Sexually Transmitted Infection 7 We defined the prevalence as the proportion of positive tests among the conclusive (positive and negative) tests results. 3 -"adolescent, literate, never married" 4 -"over 35, married, media access" 5 -"adolescent, illiterate, never married" 6 -"20-35 years, married, media access"…”
Section: Discussionmentioning
confidence: 99%
“…Clustering analysis, which is an unsupervised machine learning technique, allows us to identify similarity patterns and find hidden sub-groups of people with potentially different risk levels and drivers of having or acquiring HIV [2]. In a previous study, we investigated differences between SSA countries and identified sociobehavioural profiles that coincided with a high HIV prevalence and incidence at the country level [3]. However, this past study did not consider sub-national differences.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have shown that clustering analysis allows to identify similarity patterns and find hidden sub‐groups of people with potentially different risk levels and drivers of having or acquiring HIV [3]. When comparing sub‐Saharan African (SSA) countries, characteristic sociobehavioural profiles of the populations were found to coincide with the level of HIV prevalence and incidence in the countries [4]. Within certain SSA countries, high‐risk groups have been studied, but the studies have mainly focused on women [5‐7] and the spatial distribution of the identified groups across the country has not been examined.…”
Section: Introductionmentioning
confidence: 99%